Correlation High-Sensitivity Troponin-I and Length of Stay Acute Myocardial Infarction Patients Dr. Wahidin Sudirohusodo Hospital - Sari, Ni Putu Yunita Puspitra; Wibawa, Sulina Yanti; T. Lopa, Amaliyah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Acute myocardial infarction is a part of acute coronary syndrome, which is characterized by reduced coronary blood flow causing no oxygen supply for more than 20 minutes. High-sensitivity Troponin-I test detects heart abnormalities with minimal injury to the heart muscle. The length of stay indicates the number of days a patient is hospitalized in one treatment period. This study aims to analyze the correlation between high-sensitivity Troponin-I levels and the length of stay of acute myocardial infarction patients. A retrospective analytic observational study using medical records data with a cross-sectional design. A total of 111 patients were involved in the period of January 01 to December 31, 2022. Statistical analysis using Kolmogorov-Smirnov test and Spearman's correlation test. A correlation test showed a significant correlation between high-sensitivity Troponin-I and length of stay in NSTEMI and STEMI patients with p=0.131 (p>0.05) and p=0.415 (p>0.05), respectively. This study found no significant correlation between high-sensitivity Troponin-I levels and the length of stay of acute myocardial infarction patients.